2015
DOI: 10.1146/annurev-nutr-121214-104422
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability: Assessing Glycemia Differently and the Implications for Dietary Management of Diabetes

Abstract: The primary therapeutic target for diabetes management is the achievement of good glycemic control, of which glycated hemoglobin (HbA1c) remains the standard clinical marker. However, glycemic variability (GV; the amplitude, frequency, and duration of glycemic fluctuations around mean blood glucose) is an emerging target for blood glucose control. A growing body of evidence supports GV as an independent risk factor for diabetes complications. Several techniques have been developed to assess and quantify intrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 240 publications
0
41
0
1
Order By: Relevance
“…Specifically, the LC diet achieved significant, greater effectiveness at mitigating short-term GV assessed by using CONGA-1 and CONGA-4 to achieve a more physiologically stable blood glucose profile. GV (a measure of the amplitude, frequency, and duration of diurnal glucose fluctuations), including postprandial glucose excursions, is emerging as independent risk factors for diabetes complications (12,13,(43)(44)(45)(46). Collectively, these results suggest that an LC diet may have greater usefulness for optimizing glycemic control and preventing diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the LC diet achieved significant, greater effectiveness at mitigating short-term GV assessed by using CONGA-1 and CONGA-4 to achieve a more physiologically stable blood glucose profile. GV (a measure of the amplitude, frequency, and duration of diurnal glucose fluctuations), including postprandial glucose excursions, is emerging as independent risk factors for diabetes complications (12,13,(43)(44)(45)(46). Collectively, these results suggest that an LC diet may have greater usefulness for optimizing glycemic control and preventing diabetes complications.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses of previous trials have suggested that very-lowcarbohydrate diets promote less-favorable LDL cholesterol responses than do traditional high-carbohydrate, low-fat (HC) diets (4,5). Previous studies have also limited the assessment of glycemic control to glycated hemoglobin (HbA1c) (6)(7)(8)(9)(10)(11); frequently without an objective quantification of diabetes medication changes or the assessment of glycemic variability (GV), which is an emerging independent risk factor for diabetes-related complications (12,13). Moreover, very-low-carbohydrate diets have typically been assessed without the inclusion or control of physical activity as part of a comprehensive lifestyle-modification program (6)(7)(8)(9)11).…”
Section: Introductionmentioning
confidence: 99%
“…The dietary management is also important to minimize the glycemic variability, which is the measure of the of blood sugar concentration changes over time. 54 An uncontrolled blood sugar concentration is the major risk factor in the development of T2DM complications such as retinopaty, neuropathy, nephropathy and cardiovascular diseases. [55][56][57][58] It is important to make healthier nutritional choices to prevent these complications, which are associated with high economic, social and personal costs.…”
Section: Discussionmentioning
confidence: 99%
“…The EASD consequently recommends the the consumption of high-fiber, low-GI foods as CHO source. 54 Dietary amino acids contribute to the de novo synthesis of glucose through gluconeogenesis and participate in the re-cycling of glucose carbon via the glucose-alanine cycle. 60 However, dietary proteins have a minimal impact on glycemia and insulin secretion compared to CHOs 61 and a high-quality protein supplementation has been suggested during a weight loss program to preserve muscle mass, to improve glycemic regulation and to maintenaneuglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting plasma glucose (FPG) and plasma glycated hemoglobin (HbA1c) levels are common measures used for diabetes diagnosis and assessment of glycemic control in clinical practice for diabetes measurement [6]. FPG indicates plasma glucose levels after fasting for 8–12 hours [7] and is often used in clinical practice for high accessibility and economic feasibility to obtain immediate information.…”
Section: Introductionmentioning
confidence: 99%